High-strength geotextile and preparation method thereof
By forming a titanium dioxide hybrid silica sol protective layer on the polypropylene geotextile, the problem of insufficient aging resistance performance of the polypropylene geotextile is solved, and its light resistance and acid-base/metal ions resistance are improved, which enhances the performance in complex environments. Safety and long-term effectiveness.
Patent Information
- Application Number
- CN202411273386.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2024-12-13
AI Technical Summary
Polypropylene geotextiles have insufficient aging resistance during application, which is prone to ultraviolet aging and degradation, and fluorine-containing raw materials may cause environmental pollution.
Titanium dioxide hybrid silica sol is used as the protective layer to form a high-strength geotextile through impregnation finishing and drying, which improves its photo-aging resistance and acid-base/metal ion resistance.
It significantly improves the photo-aging performance and UV radiation resistance of geotextiles, enhances safety and long-term effectiveness in complex environments, reduces contact with metal ions, and extends the service life of geotextiles.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of geosynthetics, and particularly relates to a high-strength geotextile and a preparation method thereof. Background Art
[0002] Geotextile, also known as geotextile, is a permeable geosynthetic material made of synthetic fibers through needle punching or weaving. Mechanical properties are the most basic and important properties of geotextile in engineering applications. The durability of geotextile directly affects the reliability and safety of the project.
[0003] Compared with other plastics, polypropylene geotextile has good mechanical properties and processing properties, such as high modulus, high elongation, acid and alkali resistance, freeze-thaw resistance, light weight, low cost and other advantages, especially in high-cold frozen soil, alkaline soil and high temperature and high humidity climate environment has important application value. However, polypropylene geotextile is prone to ultraviolet aging degradation during application. In order to improve the aging resistance of geotextile, the patent application with publication number CN107215049A discloses a high-strength anti-aging warp knitted composite geotextile and a preparation method of its anti-aging layer, the composite geotextile includes an upper woven geotextile layer and a lower non-woven fabric layer, the woven geotextile layer and the non-woven fabric layer are connected by a polyester connecting line, and the outer surface of the composite geotextile is coated with an anti-aging layer. The composite geotextile has the characteristics of good anti-puncture performance, high strength, large modulus, low elongation, and good aging resistance and wear resistance. However, it uses fluorine-containing raw materials such as fluorocarbon acrylate emulsion, and the geotextile containing fluorine raw materials may cause environmental pollution problems. Summary of the invention
[0004] The object of the present invention is to provide a high-strength geotextile and a preparation method thereof, so as to solve the problem that the aging resistance of polypropylene geotextile is insufficient.
[0005] The purpose of the present invention can be achieved through the following technical solutions: A high-strength geotextile comprises a polypropylene geotextile and a protective layer. The protective layer is formed by impregnating and finishing the polypropylene geotextile with titanium dioxide hybrid silica sol and drying it.
[0006] A method for preparing a high-strength geotextile comprises the following steps: The polypropylene geotextile is immersed in titanium dioxide hybrid silica sol for impregnation finishing for 30-40 minutes, and dried at 80° C. to constant weight to obtain a high-strength geotextile.
[0007] Furthermore, the titanium dioxide hybrid silica sol is prepared by the following steps: Ethanol, tetraethyl orthosilicate, long-chain alkyl silane, vanillin-modified silane and water were mixed, stirred at 500 rpm for 25 min, hydrochloric acid was added to adjust the pH value to 3, stirring was continued for 2 h, and then tetrabutyl titanate was added dropwise, stirred at 400 rpm for 48 h, and allowed to stand for 72-80 h to obtain titanium dioxide hybrid silica sol.
[0008] Furthermore, the long-chain alkyl silane is one of octyltriethoxysilane, dodecyltriethoxysilane and hexadecyltrimethoxysilane.
[0009] Furthermore, the molar ratio of ethanol, tetraethyl orthosilicate, long-chain alkyl silane, water and tetrabutyl titanate is 20:1:0.2:10:1; the ratio of the added amount of vanillin modified silane to the amount of tetraethyl orthosilicate is 1 mol:40-50 g.
[0010] Further, the vanillin-modified silane is prepared by the following steps: Vanillin and aminosilane coupling agent are added to tetrahydrofuran, sodium sulfate is added and stirred for reaction, after the reaction is completed, the mixture is filtered, and the solvent is removed by rotary evaporation to obtain vanillin modified silane. The Schiff base condensation reaction of vanillin and primary amine has the advantages of mild conditions, rapidity, convenience and high yield.
[0011] Furthermore, the aminosilane coupling agent is one of γ-aminopropyltriethoxysilane and N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane.
[0012] Furthermore, the molar ratio of vanillin to aminosilane coupling agent is 1:1.
[0013] Furthermore, the polypropylene geotextile is a polypropylene needle-punched geotextile; The needle density of polypropylene needle-punched geotextile is 300 needles / m 2 The acupuncture depth is 8 mm.
[0014] Beneficial effects of the present invention: The invention prepares a high-strength geotextile, which is prepared by taking polypropylene geotextile and titanium dioxide hybrid silica sol as raw materials through impregnation, finishing and drying.
[0015] In order to solve the problem of poor aging resistance of polypropylene geotextile made of polypropylene as raw material, the titanium dioxide hybrid silica sol in the present invention uses tetraethyl orthosilicate, long-chain alkyl silane, vanillin-modified silane and tetrabutyl titanate as raw materials, and introduces titanium dioxide into the protective layer. Titanium dioxide, as a semiconductor material, has the advantages of low cost, good stability, large specific surface area, good light absorption performance, and high surface activity, which can improve the light aging resistance of high-strength geotextile. Depending on the usage scenario, such as mines with high metal ion content, the protective layer in the present invention uses silica sol as the main material to introduce organic siloxane raw materials with different properties to improve the acid, alkali / metal ion resistance of high-strength geotextile.
[0016] In the present invention, the polypropylene geotextile is impregnated and finished with titanium dioxide hybrid silica sol, and a protective layer is formed after drying, thereby improving the strength, acid and alkali / metal ion resistance and ultraviolet radiation resistance of the geotextile product, and enhancing the safety and long-term effectiveness of the high-strength geotextile in complex and harsh environments. DETAILED DESCRIPTION
[0017] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0018] Example 1 This embodiment provides a method for preparing a high-strength geotextile, comprising the following steps: Vanillin and γ-aminopropyltriethoxysilane were added to tetrahydrofuran, sodium sulfate was added and stirred for 4 hours, and after the reaction was completed, the reaction was filtered and the solvent was removed by rotary evaporation to obtain vanillin-modified silane. The ratio of vanillin, γ-aminopropyltriethoxysilane, tetrahydrofuran and sodium sulfate was 1 mmol: 1 mmol: 10 mL: 1 g.
[0019] Ethanol, tetraethyl orthosilicate, octyl triethoxysilane, vanillin modified silane and water were mixed, stirred at 500 rpm for 25 min, hydrochloric acid was added to adjust the pH value to 3, stirring was continued for 2 h, and then tetrabutyl titanate was added dropwise, stirred at 400 rpm for 48 h, and allowed to stand for 72 h to obtain titanium dioxide hybrid silica sol. The molar ratio of ethanol, tetraethyl orthosilicate, octyl triethoxysilane, water and tetrabutyl titanate was 20:1:0.2:10:1; the ratio of the amount of vanillin modified silane added to the amount of tetraethyl orthosilicate was 1 mol:40 g.
[0020] Polypropylene needle-punched geotextile (needle density of 300 thorns / m 2, the needle-punching depth is 8mm;) immersed in titanium dioxide hybrid silica sol for impregnation finishing for 30 minutes, and dried to constant weight at 80°C to obtain a high-strength geotextile. Among them, the breaking strength of polypropylene staple fibers in polypropylene needle-punched geotextile is 6.2cN / dtex, and the breaking elongation is 16%.
[0021] Example 2 This embodiment provides a method for preparing a high-strength geotextile, comprising the following steps: Vanillin and γ-aminopropyltriethoxysilane were added to tetrahydrofuran, sodium sulfate was added and stirred for 4 hours, and after the reaction was completed, the reaction was filtered and the solvent was removed by rotary evaporation to obtain vanillin-modified silane. The ratio of vanillin, γ-aminopropyltriethoxysilane, tetrahydrofuran and sodium sulfate was 1 mmol: 1 mmol: 10 mL: 1 g.
[0022] Ethanol, tetraethyl orthosilicate, octyl triethoxysilane, vanillin modified silane and water were mixed, stirred at 500 rpm for 25 min, hydrochloric acid was added to adjust the pH value to 3, stirring was continued for 2 h, and then tetrabutyl titanate was added dropwise, stirred at 400 rpm for 48 h, and allowed to stand for 75 h to obtain titanium dioxide hybrid silica sol. The molar ratio of ethanol, tetraethyl orthosilicate, octyl triethoxysilane, water and tetrabutyl titanate was 20:1:0.2:10:1; the ratio of the amount of vanillin modified silane added to the amount of tetraethyl orthosilicate was 1 mol:45 g.
[0023] Polypropylene needle-punched geotextile (needle density of 300 thorns / m 2 , the needle puncture depth is 8mm;) immersed in titanium dioxide hybrid silica sol for impregnation finishing for 32min, and dried at 80℃ to constant weight to obtain a high-strength geotextile.
[0024] Example 3 This embodiment provides a method for preparing a high-strength geotextile, comprising the following steps: Vanillin and γ-aminopropyltriethoxysilane were added to tetrahydrofuran, sodium sulfate was added and stirred for 4 hours, and after the reaction was completed, the reaction was filtered and the solvent was removed by rotary evaporation to obtain vanillin-modified silane. The ratio of vanillin, γ-aminopropyltriethoxysilane, tetrahydrofuran and sodium sulfate was 1 mmol: 1 mmol: 10 mL: 1 g.
[0025] Ethanol, tetraethyl orthosilicate, octyl triethoxysilane, vanillin modified silane and water were mixed, stirred at 500 rpm for 25 min, hydrochloric acid was added to adjust the pH value to 3, stirring was continued for 2 h, and then tetrabutyl titanate was added dropwise, stirred at 400 rpm for 48 h, and allowed to stand for 80 h to obtain titanium dioxide hybrid silica sol. The molar ratio of ethanol, tetraethyl orthosilicate, octyl triethoxysilane, water and tetrabutyl titanate was 20:1:0.2:10:1; the ratio of the amount of vanillin modified silane added to the amount of tetraethyl orthosilicate was 1 mol:50 g.
[0026] Polypropylene needle-punched geotextile (needle density of 300 thorns / m 2 , the needle puncture depth is 8mm;) immersed in titanium dioxide hybrid silica sol for impregnation finishing for 40min, and dried at 80℃ to constant weight to obtain a high-strength geotextile.
[0027] Example 4 Compared with Example 3, in this example, γ-aminopropyltriethoxysilane is replaced with N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, and the other raw materials and preparation process remain unchanged.
[0028] Example 5 Compared with Example 3, in this example, octyltriethoxysilane is replaced with dodecyltriethoxysilane, and the other raw materials and preparation process remain unchanged.
[0029] Example 6 Compared with Example 3, in this example, octyltriethoxysilane is replaced with hexadecyltrimethoxysilane, and the other raw materials and preparation process remain unchanged.
[0030] Comparative Example 1 Compared with Example 3, this comparative example does not add octyltriethoxysilane, and the other raw materials and preparation process remain unchanged.
[0031] Comparative Example 2 Compared with Example 3, this comparative example does not add vanillin-modified silane, and the other raw materials and preparation process remain unchanged.
[0032] Comparative Example 3 Compared with Example 3, in this comparative example, the titanium dioxide hybrid silica sol is replaced by titanium dioxide hydrosol, and the titanium dioxide hydrosol is prepared by the following steps: 200 mL of titanium dioxide hydrosol was prepared using butyl titanate, glacial acetic acid and water as raw materials, wherein the mass fraction of tetrabutyl titanate was 13% and the mass fraction of glacial acetic acid was 20%.
[0033] Tetrabutyl titanate and half of the total amount of glacial acetic acid are mixed to obtain a first mixed solution, and then the remaining glacial acetic acid and water are mixed to obtain a second mixed solution. The second mixed solution is added dropwise to the first mixed solution, and the mixture is stirred for 50 minutes to obtain a titanium dioxide hydrosol.
[0034] Polypropylene needle-punched geotextile (needle density of 300 thorns / m 2 , the needle puncture depth is 8mm;) immersed in titanium dioxide hybrid silica sol for impregnation finishing for 40min, and dried at 80℃ to constant weight to obtain a high-strength geotextile.
[0035] The samples prepared in Examples 1 to 6 and Comparative Examples 1 to 3 were subjected to natural aging tests, and weather resistance tests were performed according to the method in GB / T3681.1-2021 to test the fracture strength retention rate. The test results are as follows: .
[0036] From the test results, it can be seen that in the natural aging test, the geotechnical samples have a good fracture strength retention rate over time. As time goes by, the fracture strength of Examples 1 to 9 remains at a high level with little difference.
[0037] In order to further test the performance of the sample, the copper ion resistance test of the sample was added: The sample was immersed in a saturated copper nitrate solution at 25°C, taken out after 82 hours, and then placed in a constant temperature oven at 120°C for 18 days to test the change in its strength to characterize the copper ion resistance of the polypropylene geotextile. The test results are shown in Table 2 below: .
[0038] It can be seen from the test results that when the polypropylene needle-punched geotextile of the same material is selected for testing, the overall performance of the geotextile sample is affected after soaking in different sols for soaking treatment. The protective layer formed on the surface of the geotextile after soaking in the sol has a good protective effect, which can reduce the contact between the polypropylene fiber of the geotextile and the metal ions, so that the geotextile maintains a good strength. Copper ions are easily adsorbed by titanium dioxide (Comparative Example 3 is pure titanium dioxide hydrosol), resulting in catalytic thermal oxidation reaction during the subsequent thermal aging test, which accelerates the aging of the geotextile. It is known that the introduction of long-chain silane coupling agents can improve the hydrophobicity of the protective layer. According to the comparison between Example 3 and Comparative Example 1, it can be seen that the improvement of hydrophobicity can hinder the penetration of metal ions and thus improve the copper ion resistance of the geotextile. According to the comparison between Example 3 and Comparative Example 1, the introduction of vanillin-modified silane can hinder the subsequent thermal oxidation reaction. The Schiff base structure in the vanillin-modified silane can form a coordination bond with copper ions, reduce the presence of free copper ions, and maintain a good strength of the geotextile.
[0039] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0040] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A high-strength geotextile, characterized in that: The invention comprises a polypropylene geotextile and a protective layer, wherein the protective layer is formed by impregnating and finishing the polypropylene geotextile with titanium dioxide hybrid silica sol and drying it.
2. A method for preparing the high-strength geotextile according to claim 1, characterized in that: The steps include: The polypropylene geotextile is immersed in titanium dioxide hybrid silica sol for impregnation finishing for 30-40 minutes, and dried at 80° C. to constant weight to obtain a high-strength geotextile.
3. The method for preparing a high-strength geotextile according to claim 2, characterized in that: The titanium dioxide hybrid silica sol is prepared by the following steps: Ethanol, tetraethyl orthosilicate, long-chain alkyl silane, vanillin-modified silane and water were mixed, stirred at 500 rpm for 25 min, hydrochloric acid was added to adjust the pH value to 3, stirring was continued for 2 h, and then tetrabutyl titanate was added dropwise, stirred at 400 rpm for 48 h, and allowed to stand for 72-80 h to obtain titanium dioxide hybrid silica sol.
4. The method for preparing a high-strength geotextile according to claim 3, characterized in that: The long-chain alkyl silane is one of octyltriethoxysilane, dodecyltriethoxysilane and hexadecyltrimethoxysilane.
5. The method for preparing a high-strength geotextile according to claim 3, characterized in that: The molar ratio of ethanol, tetraethyl orthosilicate, long-chain alkyl silane, water and tetrabutyl titanate is 20:1:0.2:10:1; the ratio of the added amount of vanillin modified silane to the amount of tetraethyl orthosilicate is 1 mol:40-50 g.
6. The method for preparing a high-strength geotextile according to claim 2, characterized in that: Vanillin modified silane was prepared by the following steps: Vanillin and aminosilane coupling agent are added into tetrahydrofuran, sodium sulfate is added and stirred for reaction, after the reaction is completed, the mixture is filtered, and the solvent is removed by rotary evaporation to obtain vanillin modified silane.
7. The method for preparing a high-strength geotextile according to claim 6, characterized in that: The aminosilane coupling agent is one of γ-aminopropyltriethoxysilane and N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane.
8. The method for preparing a high-strength geotextile according to claim 6, characterized in that: The molar ratio of vanillin to aminosilane coupling agent is 1:
1.
9. The method for preparing a high-strength geotextile according to claim 2, characterized in that: The polypropylene geotextile is a polypropylene needle-punched geotextile; The needle-punched density of the polypropylene needle-punched geotextile is 300 punctures / m 2 The acupuncture depth is 8mm.
Citation Information
Cited By
Polyester staple fiber for geotextile and preparation method thereof
CN121023684A
Self-cleaning hydrosol capable of preventing corrosion and ice as well as preparation method and application of self-cleaning hydrosol
CN121574579A
